(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today, safety is the most important factor in product choosing. The greatest product should be non-toxic and safe in both raw materials and final products, as well as biodegradable and easy to obtain. At the moment, eco-friendly production is receiving a lot of attention. Because of the globalisation of the world market, textile industries are facing a difficult situation in terms of quality and productivity. In today’s highly competitive environment, and as environmental standards become increasingly severe, the textile processor’s primary concern is quality and ecology. Natural fibres have gained popularity in recent years as a result of people’s desire to live in harmony with nature. Boranssus Flabelliformis fibre has the potential to be a good source of natural fibre. The fibre is collected from the sheath of the bifurcated section of the leaf stalk that joins the palm’s trunk. This fibre is widely used in India, particularly in the prefectures of Bombay and Madras. Burma, Sri Lanka, Bangladesh, China, and West Africa are among the countries that grow palm. Boranssus Flabelliformis is only commercially produced in three Indian states: Andhra Pradesh, Tamil Nadu, and Kerala. The major goals of this study are to introduce a new ecofriendly fibre in textile industry